Pengaruh Ekspor dan Pengangguran Terhadap Pertumbuhan Ekonomi di Kalimantan Timur - Permatasari, Annisa; Rachim, Abd.; Sutrisno, Sutrisno (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to determine the effect of exports and unemployment on economic growth in East Kalimantan Province in 2008-2022. This type of research is quantitative with documentation data collection techniques in the form of times series data consisting of export data, unemployment and economic growth in East Kalimantan in 2008-2022. The analysis method used in the research is multiple regression analysis. Based on the results of the t test for export variables partially and significantly affect economic growth in East Kalimantan in 2008-2022. Meanwhile, the unemployment variable has no partial and insignificant effect on economic growth in East Kalimantan in 2008-2022. Furthermore, the simultaneous significant test results have a significant effect on the economic growth variable (Y) in East Kalimantan in 2008-2022. Based on the coefficient test, exports and unemployment had an effect of 48.2% on the dependent variable of economic growth. While the remaining 51.8% is influenced by other variables not examined in this study.